Force loading on molecular clutches governs the stability of cell lamellipodia - Ruihao Xue; Lezi Kang; Yonggang Chen; Haoxiang Yang; Hongyuan Jiang; Ze Gong (Proceedings of the National Academy of Sciences, 2026)
Cells use lamellipodia, thin actin-rich membrane protrusions, to probe the mechanical properties of their microenvironment. During mechanosensing, lamellipodia often exhibit dynamic instability in the form of protrusion-retraction cycles. However, how this mechanical instability arises during mechanotransduction remains poorly understood. Here, we develop a minimal mechanochemical model for lamellipodial dynamics that integrates membrane deformation, myosin contractility, and binding kinetics of adhesion molecules (molecular clutches). Through stochastic simulations and analytical mean-field analysis, we demonstrate that both loading rate and force magnitude applied by myosin-driven retrograde flow control the clutch binding kinetics, governing lamellipodial stability and cellular mechanosensing. Specifically, a slow loading rate promotes sustained clutch engagement and traction buildup, while a high force magnitude ruptures bound clutches. Their temporal interplay gives rise to protrusion-retraction cycles in lamellipodia. Furthermore, the model predicts a biphasic response to myosin perturbation, consistent with quantitative experimental observations. Overall, the theoretical model highlights force loading as the key mechanical input driving lamellipodial instability and cellular mechanosensing, advancing our understanding of mechanotransduction during cell spreading.